2018
DOI: 10.14419/ijet.v7i3.2.14568
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Deformation State of a Composite Cable Space Frame Structures with a Photogrammetric Method

Abstract: The article presents experimental study results of the deformation state of composite cable space frame structures, including composite steel-concrete structures. Composite cable space frame structures are three-dimensional roof framing of long-span buildings. The designed constructions are a new type of roof framing structures and consist of typical composite steel-concrete modules connected with steel cable elements. The operation of composite cable space frame structures under load is characterised by geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…To simplify the equation of the system, the influence of various factors on the above-mentioned forces that occur in the reinforced concrete part (top chord) of the composite steel and concrete grid structure was experimentally obtained. Experimental (Storozhenko et al 2018), as well as theoretical studies, showed that of the total evenly distributed load of intensity 𝑞 applied to the top chord of the composite steel and concrete grid structure, only 4-9% affects the values of the component equations 𝑀 𝑥 , 𝑀 𝑦 , 𝐻, 𝑉 𝑥 and 𝑉 𝑦 , which corresponds to the stress-strain state during bending. The rest 91-96% of the load 𝑞 falls on the components 𝑁 𝑥 , 𝑁 𝑦 , 𝑆 𝑥 and 𝑆 𝑦 , and this corresponds to the «momentless» stress-strain state.…”
Section: Resultsmentioning
confidence: 99%
“…To simplify the equation of the system, the influence of various factors on the above-mentioned forces that occur in the reinforced concrete part (top chord) of the composite steel and concrete grid structure was experimentally obtained. Experimental (Storozhenko et al 2018), as well as theoretical studies, showed that of the total evenly distributed load of intensity 𝑞 applied to the top chord of the composite steel and concrete grid structure, only 4-9% affects the values of the component equations 𝑀 𝑥 , 𝑀 𝑦 , 𝐻, 𝑉 𝑥 and 𝑉 𝑦 , which corresponds to the stress-strain state during bending. The rest 91-96% of the load 𝑞 falls on the components 𝑁 𝑥 , 𝑁 𝑦 , 𝑆 𝑥 and 𝑆 𝑦 , and this corresponds to the «momentless» stress-strain state.…”
Section: Resultsmentioning
confidence: 99%
“…2), which ensure efforts distribution in structure elements so that the top chord will be only in compression and the bottom chord in tension. In [12] described the results of research, the task of which was to determine the geometrical parameters of curvature of the new space composite structure with pinnedpinned support (Fig. 2, a).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers focus mainly on the study of the stress-strain state of beams, columns, slabs, bridge structures, structures for metallurgical and mining industry, etc. [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Justification and the selection of light concrete [2] for this construction type was based on the selection of physical and mechanical characteristics to ensure normal work throughout the period of operation. Characteristics of concrete samples were determined in two ways: a test of 100×100mm cubes and cylinders of 400mm height and 100mm in diameter (Fig.…”
Section: Requirements For Light Concretementioning
confidence: 99%